Increasing Understanding of Preparation of Financial Statements in Increasing the Competitiveness of Micro, Small and Medium Enterprises in Celuk Village - Ni Putu Budiadnyani; Putu PRA Dewi; I Gusti AAP Indraswari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Public awareness for entrepreneurship by taking advantage of existing opportunities is not followed by understanding and knowledge about the importance of managing a business well. The business community is still not aware of the importance of good financial records based on applicable standards. Recording of financial transactions is not done properly. Transactions that should be recorded may not be recorded. This underlies the socialization and education of the preparation of financial reports for micro, small and medium enterprises (MSMEs). This activity is expected to increase knowledge of the importance of compiling financial reports in running a business. Financial transactions that are arranged in good financial reports can increase the potential for MSME competitiveness.